COMPETITIVEVENESS STRATEGIES OF INDONESIA PANGASIUS FILLET - Arfin Ramadhan; Ruddy Suwandi; Wini Trilaksani (School of Business, IPB University (SB-IPB), 2016)
Pangasius fillet industry in Indonesia that has grown in recent years will face the ASEAN regional competitiveness that began in late 2015. To face competitiveness from other countries, especially Vietnam as the largest Pangasius fillet producer, this study was carried out with regard to internal and external factors as a consideration in determining future strategies. This study aims to generate alternative competitiveness strategies of Pangasius fillet through descriptive analysis, SWOT, and AHP. The analysis result of internal forces obtains the total scores of 2.645 and external forces with the score of 2.505; this means that suggested strategy belongs to hold and maintain category. AHP analysis shows that alternative strategy with the highest score consecutively is the development of aquaculture technology for quality and efficient raw material, institutional strengthening of fish farmers and suppliers, diversification and product innovation, encouragement in investment on an integrated Pangasius fillet industry, branding of the Indonesian yellow fillet. The main objective of the strategy is focusing on the continuity of production and fulfillment of consumer preferences in order to create stability of supply and demand.Keywords: AHP, competitiveness, Pangasius fillet, SWOT